ANALISIS PENDAPATAN USAHATANI JAHE (ZINGIBER officinale) Di Kecamatan Liang Anggang Kota Banjarbaru Provinsi Kalimantan Selatan - Fenny Refiana (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2021)
The research aimed to determine the explicit cost, revenue, income, and feasibility obtained from ginger farming. This research was conducted for 3 months from June 2020 to September 2020 in Liang Anggang District Banjarbaru City South Kalimantan Province. This research uses a case study method of farmers who do ginger farming, which only has one person in this research location. From this research, it was found that the total explicit cost is Rp. 66.475.000, total revenue is Rp. 158.525.000 and the total income is Rp. 225.000.000. Also ginger is a plant that deserves to be cultivated because R/C > 1, which is 3.38, which means that for every Rp. 100, - issued, you will receive an income of Rp. 338,-. And efforts that can be made to increase income are by increasing the area of ginger plants and intensive care to prevent rhizome rot to increase ginger production